Soaking the middle class : suburban inequality and recovery from disaster - Rhodes, Anna Catherine; Besbris, Max (Russell Sage Foundation, 2022)
"Soaking the Middle Class is about many families recovered from Hurricane Harvey. The book focuses on households in Friendswood, TX, a middle-class suburb of Houston, because places like Friendswood are becoming more vulnerable to climate-related disasters. How does this vulnerability play out? Presumably a middle-class, well-resourced community like Friendswood would be able to recover quickly. But as middle-class places have become more vulnerable, they have also become more unequal, with more households facing financial precarity and downward mobility. How households in places like Friendswood recover is therefore increasingly central to understanding stratification in the U.S. As the authors show, the recovery process amplifies existing inequalities instead of reducing them, encourages staying in risky places instead of fostering mobility away from them, and ultimately increases divisions between neighbors, making middle-class suburbs like Friendswood less cohesive and less resilient"--